Find the intergral of the following:-

Asked by uma.therighter | 13th Jun, 2009, 08:52: AM

Expert Answer:

1/(1+cotx) =sinx/(sinx+cosx) =1/2  (   1+ (sinx-cosx)(sinx+cosx) )

Now I= 1/2  (   1+ (sinx-cosx)(sinx+cosx) )dx=x/2 +1/2    (sinx-cosx)(sinx+cosx)  dx

Put sinx+cosx=t in the second term,

1/2    (sinx-cosx)(sinx+cosx)  dx=1/2     -dt/t = -1/2lnt

Hence I=x/2-1/2ln(sinx+cosx) +c

Similarily second can be solved.

Answered by  | 13th Jun, 2009, 06:43: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.